Thermal Performance of LPG Stove as Heat Source of Rotary Dryer for Drying Corn for Small Farmers - Ida Bagus Alit; I Gede Bawa Susana (The University of Lampung, 2025)
Sunlight to dry post-harvest food materials such as corn highly depends on the weather. When it is cloudy or rainy, drying automatically stops. On the other hand, biomass dryer models such as rice husks are rather difficult to regulate the drying temperature. This study aims to create a dryer model that produces uniform temperatures and is easy for small farmers to operate. It is a rotary dryer with liquefied petroleum gas (LPG) energy. This study tested a small-scale rotary dryer based on drying time to reduce water content by up to 14%. The test used corn samples weighing 10 kg, 15 kg, and 20 kg with a water content of 18%. Testing to reduce water content to 14% is based on the Indonesian National Standard. The results showed that corn samples weighing 10 kg, 15 kg, and 20 kg required time and LPG requirements of 37 minutes and 0.092 kg, 52 minutes and 0.132 kg, and 90 minutes and 0.281 kg, respectively. The drying temperatures were 54.67°C, 55.96°C, and 57.63°C, respectively. Rotary dryers are useful for small farmers in developing areas who do not yet understand the technology. The short drying time allows this dryer machine to repeatedly dry corn. Keywords: Rotary dryer, Liquefied petroleum gas, Corn drying, Drying rate.